fSTUDI EKSPLORATIF DI GARMENT - Juariah Juariah (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
WHO was recommended breastfeeding for 6 months and continued breastfeeding for the first two years of life. Breastfeeding had very important for optimal growth and development, both physical and mental and intelligence of the baby. Therefore, breastfeeding needed the attention of mothers and health workers so that the breastfeeding process can be carried out properly. Problems arise when a mother works. This study aims to explored the factors associated with exclusive breastfeeding for mothers at the workplace. The design of this study used the qualitative approach of the first stage with a qualitative study to explored the factors causing the failure of exclusive breastfeeding to working mothers. The second stage was to delivered the results of the first phase of research to produced policy recommendations related to exclusive breastfeeding for working mothers, especially workers in garment. X. The study population was all female workers who had children aged 6 - 60 months in Garment X Factory in Bogor City. The research sample for the qualitative study used a saturated sample. In this study, independent interviews were conducted with 10 breastfeeding mothers , indept interviewed with 3 people from garment management and 2 policy makers at the Bogor Health Office. Then conducted a Focus Group discussion (FGD) with 10 midwives at the health center. Qualitative analysis used content analysis with the visual construction paradigm so as to produce a construction model for the success of exclusive breastfeeding in working mothers. The results of this study found that low knowledge, management policies, working Time off period, age, husband and family support, culture, and frequency of breastfeeding were the factors that led to the success of exclusive breastfeeding. Policy recommendations suggest that management needs to facilitate lactation in the workplace and other public facilities. Increasing exclusive breastfeeding education and The monitoring used of formula milk.